INCLUSION OF DISABLED PERSONS IN THE REPUBLIC OF MACEDONIA: Social Protection and Employment Policies - Trbojevik, Svetlana; Bogoevska, Natasha (Ревија за социјална политика/Journal of Social Policy, 2015)
Social protection is determined as an activity of public interest. The state implements the social protection of citizens in accordance with the principle of social justice. The social protection is defined as a system of measures, activities and policies for prevention and overcoming the basic social risks to which the citizen is exposed throughout life, for reducing poverty and social exclusion and for strengthening citizen’s capacity for self protection.